ANALISIS PENGARUH METODE PEMBELAJARAN PRAKTIK LABORATORIUM BERDASARKAN TARGET KOMPETENSI TERHADAP PENINGKATAN SKILL PADA MATA AJAR KEPERAWATAN GAWAT DARURAT DAN MANAJEMEN BENCANA - Ummu Muntamah (Proceedings Education and Language International Conference, 2017)
This Research aim to prove that usage of conceptual method in tuition practice nursing clinical can improve attainment of competence practice seen nursing laboratory from make-up of value pass of student. This research use experiment quasi design (sham experiment) which take location in Ngudi Waluyo University Diploma III of Nursing. Population in this research is student of diploma III which nursing laboratory practice amount to 40 one who divided to become 2 group that is guided experiment group with competention target method and comparator group (control) guided with conventional method (demonstration method). Intake of sample done with samplingpurposive. Data collecting done by test laboratory practice after given by treatment. Data analysis done by making tabulation and processed by using formula of mean and done by calculation of frequency distribution presentation. Hereinafter to know value influence of usage of conceptual method of nursing laboratory tuition to attainment of interest done with statistical test t. Result of analysis indicate that test value practice higher experiment group than comparator group (control). The result shown with test of t where got by result -tcalculate (-5,390) < -ttables (-2,093) meaning statistically there are difference which significant between competition target. Keyword : competention target method, conventional (demonstration) method, competence